2019
DOI: 10.1002/jat.3828
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in endothelial cells induced by airborne fine particulate matter (<2.5 μm)

Abstract: Exposure to ambient fine particulate matter (<2.5 μm; PM2.5) increases the risk of the physiopathology of vascular diseases. However, the underlying mechanism, particularly the mitochondrial damage mechanism, of PM2.5‐induced vascular dysfunction is still unclear. In this study, we examined PM2.5‐induced alterations of mitochondrial morphology, and further demonstrated the adverse effects on mitochondrial dynamics and function in vascular endothelial cells. Consequently, cultured EA.hy926 cells were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…They found that there were obvious mitochondrial abnormalities characterized by swollen mitochondria with confusion and deformation of cristae, due to the decrease of the fusion protein mitofusin 2 (MFN2) and the increase of fission protein fission 1 (FIS1) under exposure, which implies that PM2.5 inhibited mitochondrial fusion (Miao et al, 2019). In addition, PM2.5 inhibited the proliferation of HUVECs in a dose‐dependent manner, where the abnormal mitochondrial membrane potential (ΔΨm) induced the mitochondrial permeability transport pore opening, thereby impairing adenosine triphosphate synthesis (Miao et al, 2019) (Figure 3). The mitochondria play an important role in cell metabolism, where they are involved in oxidative stress because the electron transport chain (ETC) of the mitochondria is the main source of ROS production.…”
Section: Pathophysiological Mechanisms Of Pm25‐induced Damage Of Vecsmentioning
confidence: 99%
“…They found that there were obvious mitochondrial abnormalities characterized by swollen mitochondria with confusion and deformation of cristae, due to the decrease of the fusion protein mitofusin 2 (MFN2) and the increase of fission protein fission 1 (FIS1) under exposure, which implies that PM2.5 inhibited mitochondrial fusion (Miao et al, 2019). In addition, PM2.5 inhibited the proliferation of HUVECs in a dose‐dependent manner, where the abnormal mitochondrial membrane potential (ΔΨm) induced the mitochondrial permeability transport pore opening, thereby impairing adenosine triphosphate synthesis (Miao et al, 2019) (Figure 3). The mitochondria play an important role in cell metabolism, where they are involved in oxidative stress because the electron transport chain (ETC) of the mitochondria is the main source of ROS production.…”
Section: Pathophysiological Mechanisms Of Pm25‐induced Damage Of Vecsmentioning
confidence: 99%
“…UPM contains redox-active components, such as heterocyclic polycyclic aromatic hydrocarbons (PAHs), nitro-PAHs, and various metals, which can lead to intracellular ROS generation by catalyzing Fenton's reaction [61,62]. Given that mitochondria are a major cellular source of ROS, growing evidence suggests that it is imperative to understand the effect of PM on mitochondrial structure and function [63,64]. In this regard, it has been reported that oxidative stress and mitochondrial dysfunction occur in various cell types upon exposure to UPM [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Given that mitochondria are a major cellular source of ROS, growing evidence suggests that it is imperative to understand the effect of PM on mitochondrial structure and function [63,64]. In this regard, it has been reported that oxidative stress and mitochondrial dysfunction occur in various cell types upon exposure to UPM [64,65]. Miao et al [64] suggested that PM induces endothelial toxicity through alterations in mitochondrial morphology and function, including MMP (∆Ψm) loss and mPTP opening.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a lack of detailed data on the genotoxicity of PM 2.5 in Beijing. Our previous studies found that these PM 2.5 samples from Beijing adsorbed 20 metals and 15 priority US EPA polycyclic aromatic hydrocarbons (PAHs), which is suggested to be the key toxic substances and mutagenic substances of PM 2.5 [ 24 ]. Among these, chromium, arsenic, cadmium, nickel, and lead are carcinogenic metals, while benzo(k)fluoranthene, benzo(a)pyrene benzo(a)anthracene, dibenzo(a)anthracene, and benzo(b)fluoranthene have been classified as carcinogens by the International Cancer Research Agency (IARC).…”
Section: Discussionmentioning
confidence: 99%
“…The adsorptive pollutants of soluble metals and PAHs may be closely related to the increased ROS. We have reported that transition metals and PAHs in our Beijing PM 2.5 compositions [ 24 ]. According to our report, the Beijing PM 2.5 adsorbs soluble transition metals on its surface, including iron, copper, chromium, and vanadium, which can generate ROS through Fenton type reactions.…”
Section: Discussionmentioning
confidence: 99%